Establishment and practice of hierarchical training and assessment model for nurses based on cloud platform (基于云平台护士分层培训与考核实践及效果评价) - LIANG Junni (梁俊妮); HONG Yanyan (洪艳燕); MENG Xian (孟贤); LIU Yuanyuan (刘园园) (Journal of International Translational Medicine Limited, 2021)
Objective To explore the practical effect of hierarchical training and assessment model for nurses based on cloud platform. Methods To establish a nursing training and assessment group based on the cloud platform, to implement the training and assessment for nurses at all levels, to compare and analyze the implementation rate of various training contents and the qualified rate of nursing assessment before and after the implementation of cloud platform, and to achieve the continuous quality improvement of hierarchical training and assessment. Results The utilization rate of cloud platform teaching mode in 46 clinical departments was 100. 0%. After implementation of the cloud platform, the scores of three basic theory test, degree of nurse satisfaction and score of information management quality assessment were increased(P＜0. 05). Conclusion The hierarchical training based on cloud platform can relieve the working pressure of front-line nurses, improve the teaching quality and improve the training effect. (目的 探讨基于云平台教学模式落实护理人员分层培训与考核的实践效果。方法 建立云平台护士培训与考核信息化管理小组, 落实各层级护士培训与考核。对比分析使用云平台落实护士分层培训与考核前后各项培训内容的落实率及护士考核合格率, 实现护士分层培训与考核工作的持续质量改进。结果 全院46个科室云平台教学模式使用率达100. 0%。与使用前(2018年度)相比, 使用云平台后(2019年度)护士"三基"理论考试分数、护士满意度评分和信息管理质量考核分数均提高, 差异有统计学意义(P＜0. 05)。结论 护士分层培训与云平台的使用能够缓解一线护理人员的工作压力, 改善教学质量, 同时提高培训效果。)